2016
DOI: 10.1103/physrevx.6.021028
|View full text |Cite
|
Sign up to set email alerts
|

Open-System Quantum Annealing in Mean-Field Models with Exponential Degeneracy

Abstract: Real-life quantum computers are inevitably affected by intrinsic noise resulting in dissipative nonunitary dynamics realized by these devices. We consider an open-system quantum annealing algorithm optimized for such a realistic analog quantum device which takes advantage of noise-induced thermalization and relies on incoherent quantum tunneling at finite temperature. We theoretically analyze the performance of this algorithm considering a p-spin model that allows for a mean-field quasiclassical solution and, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…The role of temperature and external noise was further considered in the context of the AQC in several papers, showing that in some cases it may be beneficial to reach the target ground state. Work has been done on comparing the AQC and classical approaches using thermal hopping [27], on the use of quantum diffusion, showing better performance than closed-system quantum annealing [28], and on the crucial role of noiseinduced thermalisation in the AQC, which can outperform simulated annealing [29]. In addition, the relation of thermally assisted tunnelling to the quantum Monte Carlo has been studied in [30], and the effect of the noise of a thermal environment [31] as well as decoherence [32] have been studied as well.…”
Section: Introductionmentioning
confidence: 99%
“…The role of temperature and external noise was further considered in the context of the AQC in several papers, showing that in some cases it may be beneficial to reach the target ground state. Work has been done on comparing the AQC and classical approaches using thermal hopping [27], on the use of quantum diffusion, showing better performance than closed-system quantum annealing [28], and on the crucial role of noiseinduced thermalisation in the AQC, which can outperform simulated annealing [29]. In addition, the relation of thermally assisted tunnelling to the quantum Monte Carlo has been studied in [30], and the effect of the noise of a thermal environment [31] as well as decoherence [32] have been studied as well.…”
Section: Introductionmentioning
confidence: 99%
“…In specific cases, however, it has been suggested that the external environment may be even beneficial in reaching the target ground state showing better performance than closed-system quantum annealing [26][27][28][29][30]. The point here is that the evolution of a far-from-thermal equilibrium spin system coupled to a large set of oscillators describing the external environment is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently speedup problem extensively has been discussed in the framework of quantum computation purposed to accelerate the solution of familiar optimization problems by using quantum hardware [71,72]. However, predicting a quantum speedup in this hardware represents a complex problem that depends on many physical parameters including size and topology of the system [73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%